2021
DOI: 10.5713/ab.20.0729
|View full text |Cite
|
Sign up to set email alerts
|

Association of growth hormone and insulin-like growth factor I genotype with body weight, dominance of body weight, and mRNA expression in Korat slow-growing chickens

Abstract: Objective: Growth hormone (GH) and insulin-like growth factor I (IGF-I) play a critical role in animal growth rates. We aimed to investigate the effect of GH and IGF-I genotypes on body weight (BW), dominance, and gene expression in slow-growing chickens at different ages.Methods: A total of 613 Korat chickens (KRs) were bred and divided into three groups by genotype -A1A1, A1A3, and A3A3 for GH and AA, AC, and CC for IGF-I. Chickens were weighed every two weeks, and liver and breast muscle tissues were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(48 reference statements)
0
1
1
1
Order By: Relevance
“…This can be due to environmental effects which may have contributed to selection for this genotypes in different population. In No significant difference was found in this study between the body weight and the genotypes which is contrary to the findings of Sinpru et al [19], where a significant difference between body weight and genotype was reported. Polymorphisms of GH gene have been reported in chickens at intron1, 3 and 4.…”
Section: Table 1 Genotype and Allele Frequency Of Gh Gene In Nigerian...contrasting
confidence: 99%
“…This can be due to environmental effects which may have contributed to selection for this genotypes in different population. In No significant difference was found in this study between the body weight and the genotypes which is contrary to the findings of Sinpru et al [19], where a significant difference between body weight and genotype was reported. Polymorphisms of GH gene have been reported in chickens at intron1, 3 and 4.…”
Section: Table 1 Genotype and Allele Frequency Of Gh Gene In Nigerian...contrasting
confidence: 99%
“…Harvey dan Daughaday (1995), menyatakan bahwa hormon pertumbuhan yang disekresikan oleh pituitari anterior dan tiroksin yang disekresikan oleh kelenjar tiroid bekerja secara simultan dalam mengontrol pertumbuhan unggas menjelang pubertas. Oleh karena itu perbedaan antara hormon jantan dan betina merupakan salah satu faktor yang sangat menentukan mengapa pertumbuhan jantan lebih besar daripada pertumbuhan ayam betina (Sinpru et al,2021).…”
Section: Bobot Tubuhunclassified
“…In addition, BW gain, feed intake, and feed conversion showed a significant increasing trend compared with the first week. Growth hormone and IGF2 genes are candidate genes for growth performance in chickens [24][25][26]. Therefore, these genes are usually considered candidate genes in the genetic analysis of complex animal traits such as growth rate, body composition, and fat deposition [27].…”
Section: Discussionmentioning
confidence: 99%